Tinjauan Kualitas Genteng Beton Sebagai Penutup Atap Dengan Bahan Tambah Serat Sabut Kelapa - Ariyani, Anggun Woro, Ir. Suhendro Trinugroho, MT, Ir. Aliem Sudjatmiko, MT (2015)
The more development of undertaken buildings which are needed to build means needing the good roof and have good quality, lightweight and waterproof. Concrete Tile is one of the good roof, but it has expensive price than other Tiles and it is heavy enough. This research means to know the addition Fiber of Coconut to flexible load, stand with water permeability, water absorption, uniform form, and concrete tile quality without admixture but with coconut fiber. The comperation of PC, mill lime, and sand to concrete tile admixtue composition namely, 1 PC : 2 KM : 2,5 PS. Wherease coconut admixtue precentage 0%; 1%; 1,5%; 2%; 2,5% from the weight of sand. Data is taken from calculating average of test result then compared with SNI 0096-2007. The result of out-character of concrete tile is smoth, right angle, no cracking, or no physical defect. The result measuring is P = 420 mm, L = 329 mm, the flate thickness = 9,56 mm, the thickness of lying = 9,86 mm, connection length = 50,8 mm, width length = 12 mm, connection height = 11,5 mm, widht of profile = 80,2 mm, depth of lying groove = 29,6 mm, number of lying groove 2. The result of impermeability concrete tile with coconut fiber 0%; 1% ; 1,5%; 2%; 2,5% all do not do permeability, the average of proporsity to the admixture of coconut fiber 0% = 9,046%; 1% = 9,667%; 1,5% = 10,202%; 2% = 9,741%; 2,5% = 11,317%. The result of heat average precentage coconut fiber 0% = 82,54%; 1% = 80,88%; 1,5% = 77,98%; 2% = 78,60%; 2,5% = 80,18%. The average flexure load test to the percentage of coconut fiber 0% = 103,23 kg; 1% = 107,59 kg; 1,5% = 116,32 kg; 2% = 119,22 kg; 2,5% = 126,49 kg. Form the result test means can be concluded that the more adding fiber, so it will stronger in flexure test. The research shows that the concrete tile with adding coconut fiber it has been in clasification of SNI 0096-2007 from the strenght of impermeability, as proportion, appear characteristic, and size. Whereas, from flexure character, heat absorbtion, and the prosity that hasen't been in standard.